A novel janus membrane modified by MXene for enhanced anti-fouling and anti-wetting in direct contact membrane distillation. (November 2022) - Yan, Xiaoju; Yang, Chengyu; Ma, Cong; Tao, Hui; Cheng, Shirong; Chen, Lin; Wang, Guodong; Lin, Xinping; Yao, Chengzhi
Abstract: Membrane fouling and wetting limit the applications of membrane distillation (MD) for wastewater treatment, especially when treating the wastewater with a high concentration of low surface tension substances such as oil and surfactants. In this paper, virgin polyvinylidene fluoride (PVDF) membrane was modified by polydimethylsiloxane (PDMS) to enhance anti-wetting ability. Then a thin polydopamine (PDA) layer was coated as a reaction platform for further modification. Polyethyleneimine (PEI) was cross-linked with PDA to form a uniform and stable layer, through hydrogen bonds and electrostatic interaction to immobilize hydrophilic MXene, which formed a Janus MXene-PVDF membrane. The MXene layer was the key for superoleophobicity and high liquid entry pressure (LEP) of membrane, capable of mitigating membrane fouling and wetting when dealing with low surface tension wastewater (LSTW). From the experiments results, pristine PVDF membrane showed severe fouling and wetting with flux decline and salt leakage during treatment of LSTW (surfactants containing water, oil-in-water emulsion and sodium dodecyl sulfate stabilized oil-in-water emulsion). However, under the same conditions, the Janus MXene-PVDF membrane exhibited remarkably stable flux (9.3 kg m −2 h −1, 9.1 kg m −2 h −1, 10.2 kg m −2 h −1 ) and salt rejection (almost 99.9%) after 15 h operation. Excellent fouling and wetting resistance of MXene-PVDF membrane was mainly attributed to its superhydrophilic and superoleophobic top surface (in-air water contact angle: 30.2°, under-water oil contact angle: 169.9°) and hydrophobic substrate (in-air water contact angle: 130.8°), together with high LEP value (91.1 Kpa). This study provides a viable route to fabricated a Janus membrane with outstanding fouling and wetting resistance for LSTW, oily wastewater and it has great potential for sewage treatment in the future. Highlights: Immobilize MXene through electrostatic interaction and hydrogen bonds. Janus membranes possess hydrophilicity and under water superoleophobicity. MXene nanoparticle addition increases the LEP. Modified membranes show excellent anti-fouling and anti-wetting performance.